Population-based incidence and mortality of community-acquired pneumonia in Germany. - Christian Theilacker (Public Library of Science (PLoS), 2021)
Background Little information on the current burden of community-acquired pneumonia (CAP) in adults in Germany is available. Methods We conducted a retrospective cohort study using a representative healthcare claims database of approx. 4 million adults to estimate the incidence rates (IR) and associated mortality of CAP in 2015. IR and mortality were stratified by treatment setting, age group, and risk group status. A pneumonia coded in the primary diagnosis position or in the second diagnosis position with another pneumonia-related condition coded in the primary position was used as the base cases definition for the study. Sensitivity analyses using broader and more restrictive case definitions were also performed. Results The overall IR of CAP in adults ≥18 years was 1,054 cases per 100,000 person-years of observation. In adults aged 16 to 59 years, IR for overall CAP, hospitalized CAP and outpatient CAP was 551, 96 and 466 (with a hospitalization rate of 17%). In adults aged ≥60 years, the respective IR were 2,032, 1,061 and 1,053 (with a hospitalization rate of 52%). If any pneumonia coded in the primary or secondary diagnosis position was considered for hospitalized patients, the IR increased 1.5-fold to 1,560 in the elderly ≥60 years. The incidence of CAP hospitalizations was substantially higher in adults ≥18 years with at-risk conditions and high-risk conditions (IR of 608 and 1,552, respectively), compared to adults without underlying risk conditions (IR 108). High mortality of hospitalized CAP in adults ≥18 was observed in-hospital (18.5%), at 30 days (22.9%) and at one-year (44.5%) after CAP onset. Mortality was more than double in older adults in comparison to younger patients. Conclusion CAP burden in older adults and individuals with underlying risk conditions was high. Maximizing uptake of existing vaccines for respiratory diseases may help to mitigate the disease burden, especially in times of strained healthcare resources.